Pattern of Pediatric Kidney Diseases in a Tertiary Care Center in Northeast India: a 5-year Retrospective Analysis - Barman, Himesh; Sangla, Lima; Ksoo, Rosina; Rapthap, Kamwamangika (Journal of Pediatric Nephrology, 2018)
Introduction: The pattern of kidney diseases in children may vary from place to place and is not documented in most parts of India including ours. Documenting the spectrum may be important as it can have several uses. Materials and Methods: This hospital-based retrospective descriptive study was done over a 5-year period. Results: Out of 8257 admissions, 556 renal admissions occurred in 326 children which accounted for 6.7% of all admissions. The mean age of the children admitted with kidney disease was 9.9±4.9 years with a gender ratio of 1:1.02. The most common diagnosis at discharge was postinfectious glomerulonephritis (n= 103, 31.6%), closely followed by nephrotic syndrome (n=98, 30.1%). Glomerulonephritis other than PIGN comprised 9.8% of the cases (n=32). Other diagnoses in a descending order were urinary tract infection (n=36, 11.0%), chronic kidney disease (n=8.0%), AKI (n=14, 4.2%), congenital anomalies of the kidney and urinary tract (CAKUT) (n=10, 3.1%), calculus (n=5, 1.5%) and others (0.9%). Conclusions: Postinfectious glomerulonephritis was the most common cause of renal admission in our series. Glomerular diseases constituted three quarters of all renal diseases. The load of tubular disorders was very low. Keywords: Chronic Kidney disease; Post streptococcal glomerulonephritis; Nephrotic Syndrome; Child.